Electrochemical determination of capsaicinoids content in soy sauce and pot-roast meat products by glassy carbon electrode modified with MXene/PDDA-carbon nanotubes/β-cyclodextrin. (August 2022) - Gu, Qianhui; Chen, Xingguang; Lu, Chaoqun; Ye, Cuizhu; Li, Wenzhe; Chu, Jiyang; Zhang, Wangang; Wang, Zhouping; Xu, Baocai
Abstract: Rapid quantification of capsaicinoids content is helpful for the spicy degree classification, standardized production, and quality control of soy sauce and pot-roast meat products. In our work, an electrochemical sensor based on MXene/PDDA-carbon nanotubes/β-cyclodextrin (MXene/PDDA-CNTs/β-CD) was prepared to detect capsaicinoids content in soy sauce and pot-roast meat products. The results showed that the sensor had good performance for determining capsaicinoids content, including a relatively wide linear range (0.1–50 μmol/L), a lower limit of detection (0.06 μmol/L), and an acceptable recovery rate (84.00–125.60%). The excellent performance of the sensor was mainly because the reasonable combination of MXene and CNTs amplified the reaction signal, and the addition of β-cyclodextrin made the composites have better dispersion on the GCE electrode. The sensor could realize the trace detection of capsaicinoids content in soy sauce and pot-roast meat products, which is of great feasibility for practical application. Highlights: The electrochemical sensor can detect capsaicinoids content quickly and sensitively. The reasonable combination of Mxene and CNTs greatly improves the sensitivity of detection. β-CD can make the composites have better dispersion.